Development Of Fiqh Learning Strategy Based On Visual Thinking Using Digital Infographics To Improve Learning Outcomes - Novitasari, Vaci; Waharjani, Waharjani (Early Publishing, 2026)
This study aims to develop and evaluate the effectiveness of digital visual media in improving the prayer practice skills of second-grade elementary school students. The research was conducted, involving 28 second-grade students. This study employed a Research and Development (R&D) approach adapted from the model proposed by Borg and Gall, consisting of needs analysis, product design, validation, revision, limited trials, and field trials. The developed product was an interactive digital visual learning media containing animated movements, audio guidance, and step-by-step instructions for performing prayer (shalat). Data were collected through observation sheets, performance assessment rubrics, questionnaires, and documentation. The results showed that the digital visual media was categorized as highly feasible based on expert validation (92% media feasibility and 94% material feasibility). Furthermore, students’ prayer practice skills significantly improved, with the average score increasing from 68 (pre-test) to 87 (post-test). The findings indicate that digital visual media effectively enhances students’ practical prayer skills and increases learning engagement.